2018
DOI: 10.1016/j.rmed.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Increased red cell distribution width: A novel predictor of adverse outcome in patients hospitalized due to acute exacerbation of chronic obstructive pulmonary disease

Abstract: Increased RDW is an independent negative prognostic factor associated with adverse outcomes after hospitalization due to AECOPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 23 publications
0
60
1
Order By: Relevance
“…In one study, an increased RDW was found to be compatible with previous studies reporting a correlation between RDW and stable COPD severity (42). In another study increased RDW was reported as an independent negative prognostic factor associated with adverse outcomes after hospitalization due to acute exacerbation of COPD (43). We also found higher RDW levels in COPD patients with acute exacerbation than in stable patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, an increased RDW was found to be compatible with previous studies reporting a correlation between RDW and stable COPD severity (42). In another study increased RDW was reported as an independent negative prognostic factor associated with adverse outcomes after hospitalization due to acute exacerbation of COPD (43). We also found higher RDW levels in COPD patients with acute exacerbation than in stable patients in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ozgul et al showed that RDW values were higher in the COPD group than in the controls [ 16 ]. This conclusion was recently supported by a study by Epstein et al, which suggested a number of explanations regarding the link between increased RDW during index exacerbation and higher readmission rates, which may be attributed to a variety of underlying metabolic abnormalities such as increased erythropoietin secretion and unrecognized acute worsening of cardiac function [ 17 ]. To date, the relationship between RDW and the occurrence of PE in COPD patients is a relatively uninvestigated area.…”
Section: Discussionmentioning
confidence: 80%
“…Tom et al 14 showed that after adjusting for anemia, age, and disease severity (PRISM III), high RDW was an independent risk factor for mechanical ventilation of children (OR 2.6; 95% CI 1.4-4.9; P = 0.004). Danny et al 31 constructed survival curves after adjusting for Charlson comorbidity index and reported that 60-day readmission for AECOPD was higher in patients with high RDW than patients with normal RDW (P = 0.0038). Moreover, results from a retrospective cohort study of MIMIC-III data including 404 eligible ARDS patients suggest that RDW ≥ 14.5% was an independent predictor of 30-day (OR 1.91, 95% CI 1.08, 3.39) and 90-day mortality (OR 2.56, 95% CI 1.50, 4.37) 13 .…”
Section: Discussionmentioning
confidence: 99%